A fatal chapter [large type] - Barrett, Lorna (Barrett, Lorna. Booktown mystery., 2015)
"Haunted by Pete Renquist's puzzling last words to her, Tricia Miles begins to consider who had a motive to kill her friend and president of the Stoneham Historical Society. Did Pete take his flirting too far, only to have a jealous husband teach him a lesson? Or did he discover something in the town's historical records that his killer wanted kept secret? Tricia is determined to get to the bottom of things before someone else becomes history"--publisher.